1974
DOI: 10.5962/bhl.title.52055
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the Longipinnate Ichthyosaurs of the Lower Jurassic of England, with descriptions of two new species (Reptilia: Ichthyosauria)

Abstract: A revision of the longipinnate ichthyosaurs of the English Lias (Lower Jurassic) estabhshes five valid species. One of these is referred to the Upper Liassic genus Stenopterygius, the others to the genus Temnodontosaurus Lydekker, 1889, which is predominantly Lower Liassic in age. Two new Lower Liassic species are described. A detailed account of the variates measured is given. Zusammenfaasung Eine Revision der longipinnaten Ichthyosaurier des englischen Lias (Untere Jura) stellt fuenf gueltige Arten auf. Eine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 1 publication
1
68
0
1
Order By: Relevance
“…This differs from some leptonectids such as Leptonectes (e.g. McGowan 1974; McGowan 1993) and Excalibosaurus (McGowan 2003), and from thunnosaurian ichthyosaurs (Motani 1999). The right tibia and fibula are visible.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This differs from some leptonectids such as Leptonectes (e.g. McGowan 1974; McGowan 1993) and Excalibosaurus (McGowan 2003), and from thunnosaurian ichthyosaurs (Motani 1999). The right tibia and fibula are visible.…”
mentioning
confidence: 77%
“…obs.) and preserved gut content of T. platyodon , T. trigonodon and T. eurycephalus indicate that these taxa occupied an apex predator niche (McGowan 1974; Massare 1987; Böttcher 1989; Godefroit 1996; McGowan 1996), whereas T. azerguensis is best regarded as a hunter of small and soft prey, even if the feeding ecology of other edentulous ichthyosaurs has been interpreted as suction feeding (Nicholls and Manabe 2004; and discussion in Sander et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic assignments of ichthyosaurs can rely on comparative ratios of the lengths of various skull elements (McGowan 1974, 1976, 1986). However, the Strawberry Bank specimens lack many key skull elements, and the orbital length and snout length ratios can be obtained only from specimens BRLSI M1399 and M1401 (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Later re-examination showed that the fish remains to belong to the Liassic holostean Pholidophorus, and identified numerous dibranchiate cephalopod hooklets (Pollard 1968). Large vertebrate remains including fish and small ichthyosaurs have been recorded as gut contents in some Jurassic ichthyosaur specimens (McGowan 1974). Cephalopods, however, represent the dominant component of most ichthyosaur gastric residues from Lyme Regis and Holtzmaden (see Pollard 1968;Keller 1976;Massare 1987;Bö ttcher 1989).…”
Section: Introductionmentioning
confidence: 99%